Promotion of sustainable commercial aquaculture in sub-Saharan Africa - Ridler, N.; Hishamunda, N.; Manning, P. (Roma (Italia), 2001)
v.2 : Investment and economic feasibility
Ilus.
Keywords: ACUICULTURA; SOSTENIBILIDAD; COMERCIO; PROYECTOS DE DESARROLLO; DESARROLLO PESQUERO